Urodynamic changes after valve fulguration alone and valve fulguration with bladder neck incision - Sanjeet Kumar Singh; Vijay Sharma; Anjana Singh (Journal of Indian Association of Pediatric Surgeons, 2019)
Aims: The aim of this study is to compare urodynamic changes after valve fulguration alone and valve fulguration with bladder neck incision (BNI). Settings and Design: A total of 81 patients with posterior urethral valve were treated at our center from July 2010 to July 2016. Patients were randomized into two groups using simple randomization. Forty patients underwent BNI in addition to valve fulguration (Group I), and the remaining 41 patients underwent conventional transurethral valve fulguration (Group II). Subjects and Methods: The exclusion criteria for both the groups were the presence of simultaneous urogenital anomalies, any neurological condition, history of any urethral manipulation, and urinary diversion. Urodynamic changes were compared in both groups postoperatively. All patients were evaluated throughout their follow-up, according to the following protocol: (a) Voiding cystourethrography at 6 weeks after surgery; (b) Renal function test and urine culture at 6 weeks and then 3 monthly; (c) Ultrasound kidney, ureter, and bladder region and urodynamics at 3 and 6 months after surgery and then yearly. Median follow-up period for Group I was 27.5 months (13–72 months) and 14 months (14.5–72 months) for Group II. Statistical Analysis Used: Statistical analysis was done using the Student's t-test for parametric data and Chi-square test for categorical variable. P ≤ 0.05 was considered as statistically significant. Results: The mean age was 7.26 years in Group I and 7.66 years in Group II at the end of follow-up. There was no statistically significant difference found regarding detrusor overactivity (P = 0.68), compliance (P = 0.052), end-filling pressure (P = 0.08), and max Pdet at Qmax (P = 0.08) in the both groups. However, there was a statistically significant difference regarding improvement of peak flow (P = 0.038) and postvoid residue (PVR) (P = 0.045) in Group I in comparison to Group II. Conclusions: Valve ablation with BNI gives statistically significant better urodynamics in voiding phase regarding flow and lesser PVR in comparison to valve ablation.